A parameterization for the radio emission of air showers as predicted by CoREAS simulations and applied to LOFAR measurements - Nelles, Anna; Buitink, Stijn; Falcke, Heino; Hörandel, Jörg R.; Huege, Tim; Schellart, Pim (Astroparticle Physics, 2015)
Measuring radio emission from air showers provides excellent opportunities to directly measure all air shower properties, including the shower development. To exploit this in large-scale experiments, a simple and analytic parameterization of the distribution of the radio signal at ground level is needed. Data taken with the Low-Frequency Array (LOFAR) show a complex two-dimensional pattern of pulse powers, which is sensitive to the shower geometry. Earlier parameterizations of the lateral signal distribution have proven insufficient to describe these data. In this article, we present a parameterization derived from air-shower simulations. We are able to fit the two-dimensional distribution with a double Gaussian, requiring five fit parameters. All parameters show strong correlations with air shower properties, such as the energy of the shower, the arrival direction, and the shower maximum. We successfully apply the parameterization to data taken with LOFAR and discuss implications for air shower experiments. © 2014 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2023-08-15
Keywords: Air shower; Cosmic rays; Lateral distribution; LOFAR; Radio emission